2020
DOI: 10.1002/yea.3460
|View full text |Cite
|
Sign up to set email alerts
|

Functional interrelationships between carbohydrate and lipid storage, and mitochondrial activity during sporulation in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae under conditions of nutrient stress, meiosis precedes the formation of spores. Although the molecular mechanisms that regulate meiosis, such as meiotic recombination and nuclear divisions, have been extensively studied, the metabolic factors that determine the efficiency of sporulation are less understood. Here, we have directly assessed the relationship between metabolic stores and sporulation in S. cerevisiae by genetically disrupting the synthetic pathways for the carbohydrate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Homozygous TPS1 deletion mutants are unable to sporulate in S288C-derived and W303 laboratory strains ( Van Aelst et al 1993 ; de Silva-Udawatta and Cannon 2001 ; Enyenihi and Saunders 2003 ; Gibney et al 2015 ; Liu et al 2020 ). However, this is not a shared phenotype to all laboratory strains as in the SK1 genetic background, we observed that 60% of tps1 Δ mutant cells are still able to sporulate, suggesting that the sporulation defect associated with this mutant may be specific to certain lab strains ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Homozygous TPS1 deletion mutants are unable to sporulate in S288C-derived and W303 laboratory strains ( Van Aelst et al 1993 ; de Silva-Udawatta and Cannon 2001 ; Enyenihi and Saunders 2003 ; Gibney et al 2015 ; Liu et al 2020 ). However, this is not a shared phenotype to all laboratory strains as in the SK1 genetic background, we observed that 60% of tps1 Δ mutant cells are still able to sporulate, suggesting that the sporulation defect associated with this mutant may be specific to certain lab strains ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another shared phenotype between tps1 Δ and tps2 Δ mutants is an inability to sporulate in the S288C background ( Sur et al 1994 ; Gibney et al 2015 ; Liu et al 2020 ). Here we similarly show that S288C tps2 Δ, Simi White tps2 Δ, and Bb32 tps2 Δ are unable to sporulate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation